2004
DOI: 10.1242/jcs.01405
|View full text |Cite
|
Sign up to set email alerts
|

Subnuclear distribution of the largest subunit of the human origin recognition complex during the cell cycle

Abstract: In eukaryotes, initiation of DNA replication requires the activity of the origin recognition complex (ORC). The largest subunit of this complex, Orc1p, has a critical role in this activity. Here we have studied the subnuclear distribution of the overexpressed human Orc1p during the cell cycle. Orc1p is progressively degraded during S-phase according to a spatio-temporal program and it never colocalizes with replication factories. Orc1p is resynthesized in G1. In early G1, the protein is distributed throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 43 publications
4
46
0
Order By: Relevance
“…9A). The results restricted the NLS to residues 240 -288, a region in which previous studies had identified a NLS at residues 259 -266 (PGRIKRKV) in transient expression assays (40). Therefore, this sequence was changed from RIKRK to GLEGV, and the resulting recombinant FH-Orc1(ϪNLS) protein was 1-6).…”
Section: Orc(1-6) Can Be Purified From Cellmentioning
confidence: 96%
See 1 more Smart Citation
“…9A). The results restricted the NLS to residues 240 -288, a region in which previous studies had identified a NLS at residues 259 -266 (PGRIKRKV) in transient expression assays (40). Therefore, this sequence was changed from RIKRK to GLEGV, and the resulting recombinant FH-Orc1(ϪNLS) protein was 1-6).…”
Section: Orc(1-6) Can Be Purified From Cellmentioning
confidence: 96%
“…Therefore, Orc1 is translocated to the nucleus where it subsequently associates with other ORC subunits. In early G 1 , Orc1 is distributed throughout the cell nucleus, but as cells progress through late G 1 and S-phase, Orc1 preferentially associates with heterochromatin, a phenomenon associated with amino acids 151-269 (40).…”
Section: Nuclear Localization Of Orc6-humanmentioning
confidence: 99%
“…Furthermore, Orc2 biochemically interacts indirectly with the heterochromatin protein 1 (HP1) in mammalian, Drosophila, and Xenopus cells (14,15,31,32). Depletion of Orc2 or Orc3 in HeLa cells results in a mitotic arrest with abnormally condensed chromosomes, lack of chromosome alignment at the metaphase plate, and spindle defects (15).…”
mentioning
confidence: 99%
“…ORC and HP1 co-localization on heterochromatin was also demonstrated in the mammalian cells [4347]. Nevertheless, it is still unclear whether ORC interact with HP1 on the same regions of heterochomatin, because depletion of the individual ORC subunits in human cells has different outcomes on HP1 localization on heterochromatin.…”
Section: Heterochromatin Formation and Transcription Regulationmentioning
confidence: 99%
“…As a result, ORC1 blocks Cyclin E-dependent centriole division, providing for a single round of centrosome duplication. Moreover, it is essential that the activity of the Cyclin E/CDK2 complex is kept inhibited until the early S phase, when Cyclin E is completely degraded, which coincides with ORC1 degradation through the ubiquitin-dependent pathway [47]. It should be noted that the mechanism of ORC involvement in centrosome duplication requires further investigation and the role of the other ORC subunits, which were detected at the centrosomes, still remain obscure.…”
Section: Centrosome Duplication and Cytokinesismentioning
confidence: 99%